The challenges and issues of undergraduate student retention and attainment in UK veterinary medical education - Jackson, Elizabeth; Armitage-Chan, E. (Association of American Veterinary Medical Colleges, 2017)
Student retention and attainment has recently been identified as a key area for development in veterinary medical education enquiry. Woodfield's research on retention and attainment across the UK disciplines has yielded some unique information about the challenges and issues of students who study veterinary medicine and related subjects. The present literature review aims to expand on Woodfield's findings and explain important issues about retention and attainment across veterinary medicine. Overall, the subject of retention and attainment in undergraduate veterinary medical education needs a great deal more empirical attention, such as data on the retention and attainment of mature and widening access students, and the effects of students being placed at remote locations during their studies. Our findings also cover some unsurprising issues: the dominance of women in a profession that is principally lead by men, the underrepresentation of black and minority ethnic (BME) students in veterinary medicine, and the effects of content overload in the veterinary medical curriculum. Based on data gathered by Woodfield and our investigation of the scholarly and gray literatures, we offer an overview of gaps in current knowledge and recommendations for further research.